2010
DOI: 10.1007/s10681-010-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for stay green trait in wheat (Triticum aestivum L.) in the ‘Chirya 3’ × ‘Sonalika’ population

Abstract: Stay green or delayed senescence is considered to play a crucial role in grain development in wheat when assimilates are limited. We identified three QTLs for stay green on the chromosomes 1AS, 3BS and 7DS using a recombinant inbred (RI) population developed by making crosses between the stay green parent 'Chirya 3' and non-stay green 'Sonalika'. The RI lines were evaluated in natural field conditions for 2 years in replicated trial. The QTL on chromosome 1A was identified in both the years, while the QTLs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 27 publications
6
83
2
1
Order By: Relevance
“…Ihsan et al (2016) also reported that growth and leaf area of all wheat varieties gradually decreased with delay in sowing. Genotypic difference in green leaf area duration and stay green character in response to heat stress is also reported by (Kumar al et., 2010). Grain yield which is the important agronomic traits for a crop is highly effected by the date of sowing or high temperature, Maximum grain yield is obtained by Raj 4101, HI1544 and HW5021 in timely sown condition but in late sown condition Lok54, Raj 4101 and DBW140 were the good performer.…”
Section: Resultssupporting
confidence: 64%
“…Ihsan et al (2016) also reported that growth and leaf area of all wheat varieties gradually decreased with delay in sowing. Genotypic difference in green leaf area duration and stay green character in response to heat stress is also reported by (Kumar al et., 2010). Grain yield which is the important agronomic traits for a crop is highly effected by the date of sowing or high temperature, Maximum grain yield is obtained by Raj 4101, HI1544 and HW5021 in timely sown condition but in late sown condition Lok54, Raj 4101 and DBW140 were the good performer.…”
Section: Resultssupporting
confidence: 64%
“…This is partly because chlorosis is an integral part of programmed senescence, where there are unavoidable tradeoffs between maintaining photosynthetic area and remobilization of nitrogen to the maturing grain (Vijayalakshmi et al, 2010). Nonetheless, relationships between yield and SG have been shown, and QTLs have been identified in mapping populations (Kumar et al, 2010;Vijayalakshmi et al, 2010; Table I). Since chlorosis is expressed heterogeneously on all aboveground organs, even within a single organ such as a leaf, it is not straightforward to parameterize.…”
Section: Stay-greenmentioning
confidence: 99%
“…Canopy temperature is an ideal trait showing a good genetic association with yield (Saint Pierre et al 2010). The relationship between yield and stay green trait have been discussed and quantitative trait loci (QTL) have been identified in mapping populations (Kumar et al 2010;Vijayalakshmi et al 2010). …”
Section: Introductionmentioning
confidence: 99%